COMPARISON OF THE REQUIREMENTS FOR CANDIDATE FOR PRESIDENT AND MEMBER OF HOUSE OF REPRESENTATIVE IN THE ELECTION LAW (BASED ON THE PERSPECTIVE OF PANCASILA) - Riana Susmayanti (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2021)
Comparison Of The Requirements For Candidate For President And Member Of House Of Representative In The Election Law (Based On The Perspective Of Pancasila). Ideally, the President and House Of Representative are free from nepotism, collusion and corruption in accordance with Law No. 28 of 1999 concerning State Adinistrators Who Are Clean And Free From Corruption, Collusion And Nepotism. However, Law No. 7 of 2017 concerning General Election imposes different conditions between candidate for President and member of House Of Representative. Former corruptors are prohibited from running for President, but can run for the member of House Of Representative on condition that they announce their status as convicted of corruption. This normative juridical research will analyze the unequal requirements of candidate for President and members of House Of Representative, while the positions for the state institutions are equal. The conceptual approach is used to analyze the requirements of candidate for President and members of House Of Representative. Primary legal materials collected through library research include statutory regulations. Furthermore, extensive and systematic (logical) interpretations are used to analyze requirements of candidate for President and members of House Of Representative in various laws and values of Pancasila.